Rural non-farm development in China and India: the role of policies and institutions - Mukherjee, Anit; Zhang, Xiaobo (International Food Policy Research Institute, 2005)
The dynamic rural nonfarm sector in China has been a major contributor to the country’s remarkable growth, while in India the growth in output and employment in this sector has been rather stagnant. The paper argues that the observed patterns in the rural nonfarm development are the results of institutional differences between the two countries, especially in their political systems, ownership structure, and credit institutions. A review of the strengths and weaknesses of the rural nonfarm economy in China and India highlights the potentials and challenges of growth in the sector.